Enteric neuronal cell therapy reverses architectural changes in a novel diphtheria toxin-mediated model of colonic aganglionosis - Bhave, Sukhada (Sci Rep, 2019)
Hirschsprung disease (HSCR) is characterized by absence of the enteric nervous system (ENS) in the distal bowel. Despite removal of the aganglionic segment, gastrointestinal (GI) problems persist. Cell therapy offers potential treatment but use of genetic models is limited by their poor survival. We have developed a novel model of aganglionosis in which enteric neural crest-derived cells (ENCDCs) express diphtheria toxin (DT) receptor. Local DT injection into the colon wall results in focal, specific, and sustained ENS ablation without altering GI transit or colonic contractility, allowing improved survival over other aganglionosis models. Focal ENS ablation leads to increased smooth muscle and mucosal thickness, and localized inflammation. Transplantation of ENCDCs into this region leads to engraftment, migration, and differentiation of enteric neurons and glial cells, with restoration of normal architecture of the colonic epithelium and muscle, reduction in inflammation, and improved survival.